Case Report: A Case Study on the Neurodevelopmental Profile of a Child With Pallister–Killian Syndrome and His Unaffected Twin - Samango-Sprouse, Carole A.; Hamzik, Mary P.; Rosenbaum, Kenneth; Khaksari, Kosar; Mitchell, Francie; Kommareddi, Ritika; Brooks, Michaela R.; Tipton, Elizabeth; Sadeghin, Teresa; Gropman, Andrea L. (Frontiers in Pediatrics, 2022)
Pallister-Killian syndrome is an uncommon genetic disorder that has broad developmental and multi-systemic effects. While medical complications are widely reported throughout the literature, research on the neurodevelopmental profile has been limited. Case reports make up the majority of the few existing studies regarding the neurodevelopmental phenotype associated with this disorder. The current case report describes a 3-year-old male with Pallister-Killian syndrome (AF), reports the neurodevelopmental evaluation of his unaffected twin brother (MF), and outlines the results of an optical imaging study on both boys. AF presents with severe developmental delays; however, he ambulates with support and engages in conversation using his communication device. Most severely impaired was AF’s speech and expressive language, with Childhood Apraxia of Speech (CAS) as a possible explanation for these severe deficits. MF, the sibling, demonstrated neurotypical abilities and often advanced scores for his age. Both subjects completed a functional near-infrared spectroscopy (fNIRS) study, revealing decreased temporal and frontal lobe function in AF and typical functioning in MF. This case report expands on the existing literature on PKS by describing variances in fraternal twin presentation and novel reporting on fNIRS findings in both boys.